2021
DOI: 10.1111/pirs.12597
|View full text |Cite
|
Sign up to set email alerts
|

From hot to cold: A spatial analysis of self‐employment in the United States

Abstract: Self‐employment is a geographical phenomenon influenced by national and regional contexts. However, the study of both contexts combined is scarce in the literature on the formation of regional clusters. Using panel data from the USA for 1998‐2018, we perform different techniques to study both contexts combined, including exploratory spatial data analysis and dynamic spatial estimations. We find evidence of spatial dependence of selfemployment rates, although it has decreased over time. Results also suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…We adopt the spatial panel data model (SPDM), a flexible model specification approach to capture possible spatial interactions of default risk on local government debts. With extensive availability of panel datasets, the SPDM has been widely applied in empirics of regional science (Almeida et al, 2021; Donfouet et al, 2018; Fingleton & Arbia, 2008; Hortas‐Rico & Rios, 2020; Santolini, 2020). The general expression of SPDM is specified as follows: Riskitgoodbreak=ρji0.3emwijRiskjtgoodbreak+Xitβgoodbreak+θji0.3emwijXjtgoodbreak+αigoodbreak+ηtgoodbreak+uit, uitgoodbreak=λij0.3emwijujtgoodbreak+εit, where the dependent variable Risk it represents the level of debt default risk of city i in year t , which is endogenously determined by neighbouring cities' behaviours, ji0.3emwijRiskjt.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We adopt the spatial panel data model (SPDM), a flexible model specification approach to capture possible spatial interactions of default risk on local government debts. With extensive availability of panel datasets, the SPDM has been widely applied in empirics of regional science (Almeida et al, 2021; Donfouet et al, 2018; Fingleton & Arbia, 2008; Hortas‐Rico & Rios, 2020; Santolini, 2020). The general expression of SPDM is specified as follows: Riskitgoodbreak=ρji0.3emwijRiskjtgoodbreak+Xitβgoodbreak+θji0.3emwijXjtgoodbreak+αigoodbreak+ηtgoodbreak+uit, uitgoodbreak=λij0.3emwijujtgoodbreak+εit, where the dependent variable Risk it represents the level of debt default risk of city i in year t , which is endogenously determined by neighbouring cities' behaviours, ji0.3emwijRiskjt.…”
Section: Methodsmentioning
confidence: 99%
“…We adopt the spatial panel data model (SPDM), a flexible model specification approach to capture possible spatial interactions of default risk on local government debts. With extensive availability of panel datasets, the SPDM has been widely applied in empirics of regional science (Almeida et al, 2021;Donfouet et al, 2018;Fingleton & Arbia, 2008;Hortas-Rico & Rios, 2020;Santolini, 2020). The general expression of SPDM is specified as follows:…”
Section: Specifications For the Spatial Interactionsmentioning
confidence: 99%
“…Recently, Alden et al (2021) have confirmed this evidence for Sweden and highlight that attitudes toward SE differ dramatically between natives and foreign-born individuals. Moreover, Almeida et al (2021) show the geographical nature of SE, which is affected by both national and regional elements. Therefore, the distinctive features of SE for different individuals in Europe (Saridakis et al, 2019), as well as the existence of significant differences in SE across Europe, highlight the importance of augmenting the scarce available evidence about this topic in the European context.…”
Section: Introductionmentioning
confidence: 99%